Gesellschaftskritik ohne Gegenstand: Axel Honneths Anerkennungstheorie aus materialistischer Perspektive - Mohan, Robin; Keil, Daniel (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
Honneths theory of recognition has been broadly discussed as a central approach of critical social theory. Taking this seriously, the article traces first the main assumptions of Honneths approach and his examination of the main structures of society and therefor of the recognition-theoretical turn. Secondly, some major objections formulated by Nancy Fraser und Christoph F. Zurn and Jean-Philippe Derantys defence of Honneths approach will be discussed. Third, the article will argue that Honneths attempt to reformulate a normative critical social theory fails to grasp its object – society – adequately.